Association Between Asthma and All-Cause Mortality and Cardiovascular Disease Morbidity and Mortality: A Meta-Analysis of Cohort Studies - Zhang, Bin; Li, Zhi-Fei; An, Zhuo-Yu; Zhang, Li; Wang, Jing-Yi; Hao, Meng-Di; Jin, Yi-Jing; Li, Dong; Song, An-Jian; Ren, Qiang; Chen, Wen-Biao (Frontiers in Cardiovascular Medicine, 2022)
Background: Asthma and cardiovascular disease (CVD) share many risk factors. Previous meta-analyses indicated that asthma is associated with an increased risk of CVD and all-cause mortality, but these studies were limited by unstandardized search strategies and the number of articles included. Objective: We sought to systematically synthesize evidence investigating the impact of asthma on all-cause mortality and CVD morbidity and mortality. Methods: we searched in PubMed and EMBASE for observational cohort studies (inception dates to November 10, 2021) that had both asthma groups and control groups. We also manually searched the reference lists of correlative articles to include other eligible studies. Data for associations between asthma and all-cause mortality and CVD morbidity and mortality were needed. Results: We summarized the findings from 30 cohort studies comprising 4,157,823 participants. Asthma patients had increased CVD morbidity (relative risk [RR] = 1.28, 95% confidence interval [CI] = 1.16–1.40) and increased CVD mortality (RR = 1.25, 95% CI = 1.14–1.38). Asthma patients also had increased risk of all-cause mortality (RR = 1.38, 95% CI = 1.07–1.77). In subgroup analyses, female asthma patients had a higher risk of CVD morbidity and all-cause mortality than male asthma patients, and late-onset asthma patients had a higher risk of CVD morbidity than early-onset asthma patients. Conclusion: Asthma patients have increased risk of all-cause mortality and CVD morbidity and mortality. This information reminds clinicians to be aware of the risk of CVD and all-cause mortality in asthma patients.